2021
DOI: 10.1101/2021.08.05.455351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bursting emerges from the complementary roles of neurons in a four-cell network

Abstract: Rhythmically active neural circuits often contain reciprocally inhibitory modules that act as half-center oscillators. In half-center oscillators, alternating burst discharges require a mechanism to transition activity from one phase to the next, which requires particular synaptic and membrane properties. Here we found that active membrane properties of specific neurons and the temporal dynamics of particular synapses both contribute to the production of a stable rhythmic motor pattern in the swim central patt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Moreover, these interneurons are not latent bursters either, as they do not burst even when perturbed with constant external currents [41]. Neurophysiological experiments on the swim CPGs [16][17][18][19][20][21][22][23] have demonstrated that their interneurons are either quiescent at most times, or become tonic-spiking during swim episodes when receiving excitatory drives from sensory cells. This strongly suggests that the slow bursting (of period ranging from 2 through 14 seconds, resp., in juvenile and grown animals) observed in the experimental studies on the swim CPGs in the sea slugs is indeed a network-level dynamical phenomenon emerging due to nonlinear interactions between the interneurons orchestrated by complex coordination of fast and slow currents, including synaptic ones.…”
Section: Conductance-based Model Of Swim Cpg Interneuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these interneurons are not latent bursters either, as they do not burst even when perturbed with constant external currents [41]. Neurophysiological experiments on the swim CPGs [16][17][18][19][20][21][22][23] have demonstrated that their interneurons are either quiescent at most times, or become tonic-spiking during swim episodes when receiving excitatory drives from sensory cells. This strongly suggests that the slow bursting (of period ranging from 2 through 14 seconds, resp., in juvenile and grown animals) observed in the experimental studies on the swim CPGs in the sea slugs is indeed a network-level dynamical phenomenon emerging due to nonlinear interactions between the interneurons orchestrated by complex coordination of fast and slow currents, including synaptic ones.…”
Section: Conductance-based Model Of Swim Cpg Interneuronsmentioning
confidence: 99%
“…In addition, there is a weak electrical synapse or a gap junction between the neurons. The gap junction was reported in the biological EI-module, which happens to be the key building block in the swim CPG of the sea slug Dendronotus iris [23]. Unlike the chemical synapses, the gap junction is bi-directional, and the corresponding current is described by an additional term I elec syn = g elec (V post − V pre ), in the voltage equation (1), where g elec ≃ 1 − 2 × 10 3 nS.…”
Section: Tonically Spiking and Quiescent Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these interneurons are not latent bursters either, as they do not burst even when perturbed with constant external currents 40 . Neurophysiological experiments on the swim CPGs [15][16][17][18][19][20][21][22] have demonstrated that their interneurons are either quiescent at most times, or become tonic-spiking during swim episodes when receiving excitatory drives from sensory cells. This strongly suggests that the slow bursting (of period ranging from 2 through 14 sec, resp., in juvenile and grown animals) observed in the experimental studies on the swim CPGs in the sea slugs is indeed a network-level dynamical phenomenon due to nonlinear interactions between the interneurons orchestrated by complex coordination of fast and slow currents, including synaptic ones.…”
Section: Introductionmentioning
confidence: 99%
“…The CPG circuits underlying their behaviors have been studied extensively in both species [16][17][18][19] . All neurons in the CPGs have been identified, and their synaptic connections have been determined with careful pairwise electrophysiological recordings [20][21][22] . The swim CPGs in these sea slugs do not include endogenously bursting pacemakers.…”
Section: Introductionmentioning
confidence: 99%